2017
DOI: 10.1111/bjd.15560
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting quality of life in patients with vitiligo: a nationwide study

Abstract: A multitude of factors significantly influence the QoL of patients with vitiligo. A better appreciation of these factors would help the management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Intriguingly, the presence of vitiligo on visible sites, such as face, neck, scalp was not associated with a poor dermatology-specific QoL, which was inconsistent with the previous studies. Several studies showed that patients had higher scores of QoL when having lesions on visible sites[22,23,25,26]. Nevertheless, there were also several studies did not find any relationship between DLQI score and visibility of lesions[6,10,27].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the presence of vitiligo on visible sites, such as face, neck, scalp was not associated with a poor dermatology-specific QoL, which was inconsistent with the previous studies. Several studies showed that patients had higher scores of QoL when having lesions on visible sites[22,23,25,26]. Nevertheless, there were also several studies did not find any relationship between DLQI score and visibility of lesions[6,10,27].…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo is the most common skin depigmentation disorder, affecting 1% of the population worldwide (Rodrigues, Ezzedine, Hamzavi, Pandya, & Harris, ). Although the extent of involvement varies widely among patients, limited involvement is much more common than generalized or widespread involvement (Bae et al., ). Therefore, localized therapy (e.g., laser treatment, topical agents, melanocyte transplantation) is as essential as systemic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Vitiligo -any type concerned -casts significant impacts on the quality of life (QOL) of patients [1]. The presence of lesions on the visible parts and the extensiveness of lesions was reported to be significantly associated with impairments in QOL [3]. Specific scales are now in place to assess the impact of vitiligo on the QOL of individual patients [4][5][6].…”
Section: Discussionmentioning
confidence: 99%